Hubungan Work Family Conflict dan Family Work Conflict Terhadap Keterlibatan Kerja Pada Ibu Bekerja di Rumah (Work From Home) di Masa Pandemi Covid-19 - Jatmika, Devi; Suryadi, Caroline Kezea (Psychopreneur Journal, 2021)
The COVID-19 pandemic has changed people's normal activities, including work. During the pandemic, it enforced people to work from home to reduce the spread of the virus. Routines that are usually carried out in the office must be carried out at home. Therefore, it requires adaptation and causes role conflicts in working mothers. The demands of the role of mother at home together with the role of workers at home may have impacts on the work involvement of mothers. The purpose of this study was to examine the relationship between work-family conflict and family-work conflict on the work involvement of mothers who work at home. The research method used non-experimental quantitative research methods. Participants in the study were mothers who worked in the Greater Jakarta area. The sample obtained was 132 respondents with an age range between 20-60 years. The sampling technique for data collection was convenience sampling technique. Data collection using a questionnaire. Work involvement variable is measured by The Utrecht Work Engagement Scale (UWES) and the scale of work-family conflict and family-work. Data analysis using Pearson correlation test technique. The results revealed that the hypothesis was not accepted, there was no relationship between work-family conflict on work involvement and there was no relationship between family-work conflict on work involvement.